Angiomatoid Spitz Nevus - Lopes, Jorge (2020)
Angiomatoid Spitz nevus is a rare tumor that combines the classic aspects of Spitz nevus with a prominent vascular component. Clinically, it presents as a pink or brownish papule, usually solitary, in the extremities of young adults. On histology, it is characterized by a proliferation of epithelioid or spindle cell melanocytes embedded in a fibrous stroma, where a dense proliferation of small vessels is evident. The differential diagnosis with malignant melanoma can be difficult, particularly with the desmoplastic variant or with those with marked regression. Its behavior is benign, as suggested by the absence of local recurrences or distant metastases during long-term follow-up.